Financial Distress Analysis in the Consumer Goods Industry Post Covid-19 Pandemic - Loupatty, Linda Grace; Atarwaman, Rita J.D.; Usmany, Alfrin E. M. (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to empirically test whether Net Working Capital to Total Assets, Retained Earnings to Total Assets, EBIT to Total Assets, and Book Value of Equity to Book Value of Total Debt have an effect on Financial Distress in companies in the Consumer Goods Industry sector listed on the Indonesia Stock Exchange after the Covid-19 pandemic using the Altman Z-Score method. The sample used consisted of 52 companies obtained through a saturated sampling technique (Census Technique). The data analysis method employed was the Modified Altman Z-Score III Model and Logistic Regression Test. The independent variables (X) in this study are net working capital to total assets, retained earnings to total assets, EBIT to total assets, and book value of equity to book value of total debt, while the dependent variable (Y) is financial distress. The data used in this study are secondary data, namely annual reports. The results of the study show that, partially, Net Working Capital to Total Assets, Retained Earnings to Total Assets, EBIT to Total Assets, and Book Value of Equity to Book Value of Total Debt do not have a significant effect on the occurrence of financial distress.